IMPLEMENTATION GUIDANCE SERVICES GROUP LEARNING DIFFICULTIES TO OVERCOME - ASMARYADI ASMARYADI (Ristekdik : Jurnal Bimbingan dan Konseling, 2018)
This study is based on problems that overcome learning difficulties. The research goal is to obtain a picture of the decline of learning kesultian sisw in SMA 1 Padangsidimpuan memalui group counseling services. The method used in this research is True experimental design with pretest-¬Posttest shape control group design. with samples of the experimental class is the first class XI IPS as many as 10 students and the control class is class XI IPS II as many as 10 students so that the total sample of 20 students. Group counseling services are conducted twice meetings and two meetings of information services, namely in the first meeting perform pretest and posttest perform all treatments. Data were analyzed using the Wilcoxon rank test signesd and Kolmogorov Smirnov 2 with the help SPSS version 20.00. From the results of the implementation is done, a significant increase is mainly posttest experiment. The findings in the experimental group and the control group there were significant increases between the posttest and posttest control experiment. On average variable learning difficulties at 143. 6000 (posttest experiment) while the control group 117.4000 (posttest control) looks very significant difference. The conclusion of this study the data processing, shows that the implementation of group counseling services can overcome learning difficulties. It is recommended for teachers to students' learning difficulties is much decreased, and a much better way of learning and implementing the spirit of learning more so that there is no learning difficulties. For further research, is expected to make a research on other learning difficulties in order to assist students in improving ways of learning through other methods. Keywords: Guidance Services Group, Learning Difficulti